2018
DOI: 10.3390/nu10070934
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Increase in Unconjugated Cinnamic Acid Concentration in Plasma Following Acute Consumption of Polyphenol Rich Curry in the Polyspice Study

Abstract: Spices that are rich in polyphenols are metabolized to a convergent group of phenolic/aromatic acids. We conducted a dose-exposure nutrikinetic study to investigate associations between mixed spices intake and plasma concentrations of selected, unconjugated phenolic/aromatic acids. In a randomized crossover study, 17 Chinese males consumed a curry meal containing 0 g, 6 g, and 12 g of mixed spices. Postprandial blood was drawn up to 7 h at regular intervals and plasma phenolic/aromatic acids were quantified vi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Ultimately, they undergo metabolism in the liver to conjugate forms—sulphates or glucuronides. Non-absorbed glycosides pass into the colon, where they are metabolized by the intestinal microbiome (e.g., flavonoids combined with rhamnose are hydrolysed by α-rhamnosidases produced by Bifidobacterium dentium [ 204 , 205 ]). Hence the final effect caused by phenolic acids in the body will depend on the content of phenolic compounds in food, their chemical form and the composition of the intestinal microflora.…”
Section: Anticancer Activity Of Ncamentioning
confidence: 99%
“…Ultimately, they undergo metabolism in the liver to conjugate forms—sulphates or glucuronides. Non-absorbed glycosides pass into the colon, where they are metabolized by the intestinal microbiome (e.g., flavonoids combined with rhamnose are hydrolysed by α-rhamnosidases produced by Bifidobacterium dentium [ 204 , 205 ]). Hence the final effect caused by phenolic acids in the body will depend on the content of phenolic compounds in food, their chemical form and the composition of the intestinal microflora.…”
Section: Anticancer Activity Of Ncamentioning
confidence: 99%
“…Cinnamic acid ( 13 ) accumulated after 24 h fermentation of GK and AW LCCs (Figure a,c). Ferulic acid attached to lignin polyphenols with xylan also have many biological activities, such as antioxidant and anti-inflammatory properties. , It is thought that dietary polyphenols can be converted into more active phenolic acid compounds by gut bacteria. , Hydroxybenzoic acid ( 10 ) and its derivatives ( 8 , 9 , and 14 ) were observed (Figure ). These compounds have well-known physiological activities in humans .…”
Section: Resultsmentioning
confidence: 99%
“…Hence, we did not observe any noticeable effects on postprandial F2-isoprostanes or on changes in vascular function with or without curry intake. While some of the polyphenols in spices, including the well-studied curcumin is poorly bioavailable, although we have recently shown that some of the secondary metabolites of polyphenols, such as cinnamic acid, with high antioxidant activity in vitro , did increase in plasma with increasing doses of curry intake (Haldar et al, 2018). Furthermore, given the large inter- and intra-individual variability in the responses in these measurements, there is a possibility that our study was not adequately powered to detect subtle differences as shown in detail in Supplementary Table 2, which included the effect sizes and the raw mean differences, along with the p -values to enable the readers to make an informed judgment.…”
Section: Discussionmentioning
confidence: 99%